Oral administration of antigens from intestinal flora anaerobic bacteria reduces the severity of experimental acute colitis in BALB/c mice - Verdù, E F; Bercik, P; Cukrowska, B; Farre-Castany, M A; Bouzourene, H; Saraga, E; Blum, A L; Corthésy-Theulaz, I; Tlaskalova-Hogenova, H; Michetti, P (Clinical and experimental immunology, 2000)
Homeostasis between indigenous intestinal flora and host response may be broken in inflammatory bowel disease. The present study explores whether repeated oral administration of intestinal flora antigens can protect mice against dextran sodium sulphate (DSS)-induced colitis. Sonicates of Gram-positive, Gram-negative, or anaerobic resident bacteria isolated from mouse intestinal flora were fed to BALB/c mice by gastric gavage, with or without cholera toxin. After four weekly doses of 1 mg of these antigen preparations (or of PBS as control), DSS colitis was induced. One week later colitis was evaluated by clinical scores and histology. Mice fed a pool of the three sonicates had decreased inflammation scores (5 (1-14); median (range)) compared with PBS-fed control animals (15 (7-19); P < 0.05). Decreased inflammation was observed in mice fed anaerobic bacteria antigens (7 (6-11); P < 0.05 versus control), but not in mice fed a pool of Gram-positive and -negative sonicates (16 (12-16)). Inflammation scores of mice fed antigens with cholera toxin were similar to those of PBS-fed control animals. DSS-induced colitis can be suppressed by oral administration of normal intestinal flora antigens containing anaerobes.
Keywords: Mice, Inbred BALB C; Intestines; kolitida; aplikace orální; Mice; Intestinal Mucosa; antigeny bakteriální; střeva; Antigens, Bacterial; anaerobní bakterie; zvířata; Bacteria, Anaerobic; Acute Disease; myši inbrední BALB C; střevní sliznice; Administration, Oral; myši; Colitis; akutní nemoc; Animals